Neuromuscular transmission modulation by A2A adenosine receptors in the SOD1G93A mouse model of amyotrophic lateral sclerosis - Fernandes, Filipe Jorge do Nascimento Xavier, 1989 (2014)
Tese de mestrado, Neurociências, Faculdade de Medicina, Universidade de Lisboa, 2013